2022
DOI: 10.21037/atm-22-2669
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of absolute lymphocyte count in patients with advanced esophageal cancer treated with immunotherapy: a retrospective analysis

Abstract: Background: Immunotherapy has become the standard of treatment for recurrent metastatic esophageal cancer (EC), and the value of efficacy predictive markers represented by programmed death-ligand 1 (PD-L1) is limited. The purpose of this study is to analyze the prognostic value of peripheral blood absolute lymphocyte count (ALC) at baseline in patients with recurrent metastatic EC treated with immunotherapy, and to further investigate the relationship between the minimal ALC value (Min ALC) and radiotherapy (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Conversely, a decrease in lymphocyte counts hampers the immune response against cancer cells [ 38 ]. The presence of lymphopenia has been shown to be correlated with an unfavorable prognosis in individuals diagnosed with cancer [ 39 ]. Consequently, the ALI, in conjunction with these factors, serves as a valuable comprehensive indicator of nutritional and inflammatory status, facilitating a deeper comprehension of patients’ functional state and offering predictive insights into survival outcomes for individuals with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a decrease in lymphocyte counts hampers the immune response against cancer cells [ 38 ]. The presence of lymphopenia has been shown to be correlated with an unfavorable prognosis in individuals diagnosed with cancer [ 39 ]. Consequently, the ALI, in conjunction with these factors, serves as a valuable comprehensive indicator of nutritional and inflammatory status, facilitating a deeper comprehension of patients’ functional state and offering predictive insights into survival outcomes for individuals with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ALC represents the state of immune function in the patient, and lymphopenia may be associated with a poor prognosis in patients receiving ICIs. Low ALC before ICI initiation is a predictor of poor response in many cancers, including lung cancer, esophageal cancer, head and neck cancer, and melanoma [ 11 , 12 , 22 , 23 , 24 ]. We previously reported that ALC was an independent biomarker of therapeutic response in patients with metastatic RCC treated with nivolumab monotherapy [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…While lymphocytes, especially CD4+ T lymphocytes and CD8+ T lymphocytes, as the most important immune cells, play an anti-tumor role by inducing the lysis and apoptosis of tumor cells ( 41 ). Lymphopenia has been demonstrated to be associated with poor prognosis in cancer patients ( 42 , 43 ). On the other hand, nutritional status is also reported as an important predictive factor of therapeutic outcomes in several types of malignancies ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%